1982
DOI: 10.1111/j.1365-2621.1982.tb10087.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Processing on the Survival of Foot‐and‐Mouth Disease Virus in Ground Meat

Abstract: Foot-and-mouth disease virus was examined for its stability during cooking in tissues from infected cattle. The Oi (CANEFA 2) serotype of foot-and-mouth disease virus survived in lymph node tissues after heating for 2 hr at 69"C, for 1 hr but not for 2 hr at 82°C and for 1.5 min but not for 0.5 hr at 90°C. Incorporation of 1% NaCl into suspensions of infected lymph nodes enhanced viral survival after heating for 0.5 hr but not for 1 hr at 90°C. The virus did not survive in either ground beef or meatballs conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Heidelbaugh and Graves (23) found that the virus in lymph nodes from infected cattle was inactivated by heating to 69°C. In contrast, Blackwell et al (24) recovered FMDV from lymph nodes of infected cattle after heating for 2 hours at 69°C, 1 hour at 80 °C, and 15 minutes at 90°C. Further, the incorporation of 1 % NaCI enhanced virus survival.…”
Section: Virus Survivalmentioning
confidence: 87%
See 1 more Smart Citation
“…Heidelbaugh and Graves (23) found that the virus in lymph nodes from infected cattle was inactivated by heating to 69°C. In contrast, Blackwell et al (24) recovered FMDV from lymph nodes of infected cattle after heating for 2 hours at 69°C, 1 hour at 80 °C, and 15 minutes at 90°C. Further, the incorporation of 1 % NaCI enhanced virus survival.…”
Section: Virus Survivalmentioning
confidence: 87%
“…Further, the incorporation of 1 % NaCI enhanced virus survival. In studies of meatballs held in nylon tubes, cooking to an internal temperature of 93.3 °C was sufficient to ensure that the virus did not survive processing (24). In further tube cooking trials, FMDV in ground beef products survived a temperature of 72 0c, but was inactivated in products cooked to an internal temperature of 79.4 °0 21 ).…”
Section: Virus Survivalmentioning
confidence: 96%
“…Because the lymphatic system removes infectious agents, inclusive of viruses from circulating blood, there is a high concentration of viruses in lymph node tissue during the viremic stage of disease. The regimen that we have described for the production of FMD-infected lymph node tissue has consistently produced infectious tissue with a mean virus titer of 4.0 log,, PFU per gram tissue (Blackwell et al, 1982b). However, subliminal quantities of FMD virus, not detectable by conventional cell culture assay systems, can produce clinical FMD in susceptible livestock.…”
Section: Preparation Of Beef Productsmentioning
confidence: 98%
“…Previous studies also demonstrated that both a product of desired characteristics and a concomitant virucidal effect could be achieved through the controlled cooking of ground beef products in flexible nylon tubes to respective core temperatures of 79.4"C and 93°C (Blackwell et al, 1982b;Blackwell et al, 1988). The processing conditions examined for their virucidal effectiveness in these studies and others are those that have been used commercially in the processing of various meat products.…”
Section: Introductionmentioning
confidence: 94%
“…The virus can persist for long periods in lymph nodes, clotted blood and bone marrow of carcasses from infected cattle (Cottral, 1969). However, methods for the production of virus-free meat products prepared from such carcasses have been reported (Heidelbaugh and Graves, 1968;McKercher et al, 1980;Blackwell et al, 1982). Effective processing has allowed the importation of some of these products into FMD-free countries.…”
Section: Introductionmentioning
confidence: 99%